Habitat disturbance can alter forest understory bird activity patterns: A regional-scale assessment with camera-traps - Fontúrbel, Francisco E.; Orellana, José I.; Rodríguez-Gómez, Gloria B.; Tabilo, Catalina A.; Castaño-Villa, Gabriel J. (Forest ecology and management, 2021)
[Display omitted] •Disturbed and regenerated forests represent 75% of the world forested area.•Habitat disturbance can alter species behavior besides its composition and abundance.•Camera traps are widely used for wildlife monitoring, but its use on bird is sporadic.•Forest disturbance altered bird daily activity patterns across foraging guilds.•Forest management and restoration should take animal behavior into account. Despite forests are a biodiversity reservoir and a wellbeing source for the humankind, they have been largely disturbed in the past decades. Disturbed and naturally-regenerated forests and forest plantations represent 75% of the world forested area, stressing the need of managing non-pristine forests. While we know that habitat disturbance alters forest structure, reducing species richness and abundances, its effects on animal behavior remain little explored. We used camera traps to test if daily activity patterns of forest birds change along a 450-km disturbance gradient in the Valdivian temperate rainforests of southern Chile. We contrasted bird activity at four conditions: old-growth and second-growth native forests, native forests subject to selective logging, and abandoned exotic plantations with native vegetation. We contrasted habitat structure among conditions and estimated activity kernels to compare bird activity. We also made activity comparisons examining bird foraging guilds (nectarivores, frugivores, and insectivores) and habitat preference (interior vs edge). Habitat structure was different among conditions, being the old-growth native stands the most contrasting habitat. Bird daily activity patterns differed among conditions as well. We observed that bird activity reaches a peak early in the morning at the old-growth native forests, at noon in the plantations, and in the afternoon at the logged forests, while it was more variable in secondary forests. We obtained similar results among bird foraging guilds, but insectivorous birds presented the most contrasting differences. Likewise, we found a similar pattern between forest interior and edge species, which was more evident for forest interior birds. Logged forests presented the largest activity differences, despite being structurally similar to second-growth stands. Forest disturbance not only alters bird species richness and abundance, but also their behavior. Bird daily activity patterns may be directly affected by daily variations in forest microclimate conditions and indirectly affected by chantes in resource availability, which may be affecting their ecological interactions. Therefore, forest management and restoration strategies should take animal behavior into account.